1973
DOI: 10.1002/ps.2780040412
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control of cattle ticks—resistance problems

Abstract: Chemical control, by dipping or spraying infested cattle with ixodicidal compounds, is the only practicable method of dealing with the cattle tick problem in the short term.Widespread exposure to ixodicidal compounds, often at subeffective concentrations, has resulted in the selection of resistant strains from tick populations.A situation has now been reached where cattle ticks in widely separated parts of the world have shown a capacity to develop resistance to most of the currently available chemical classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…To date, the control of ticks has been largely dependent upon the use of acaricides (Rodriguez-Vivas et al 2018;Nwanade et al 2020). However, due to the emergence of tick populations resistant to the acaricides (Brito et al 2011), and concerns on food and environmental pollutions (Harrison and Wilmshurst 1973;George and Davey 2004;Shanmuganath et al 2021), new approaches are being sought for effective tick control.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the control of ticks has been largely dependent upon the use of acaricides (Rodriguez-Vivas et al 2018;Nwanade et al 2020). However, due to the emergence of tick populations resistant to the acaricides (Brito et al 2011), and concerns on food and environmental pollutions (Harrison and Wilmshurst 1973;George and Davey 2004;Shanmuganath et al 2021), new approaches are being sought for effective tick control.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first reports of the use of AMZ in domestic animals was the paper by Harrison et al . (1973) which showed that this drug is a good alternative for the control of ectoparasites in cattle, especially for the treatment of tick strains resistant to organochlorine and organophosphorus pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional organochlorine and organophosphorus compounds are available in Turkeyand are uscd for the control of ectoparasites in those areas where severe infestation occurs. Continucd tiek control has rcsulted in the development of resistance to thesc chcmicals (5,10,13). A new acaricide wiıh a mode of aetion different from those of the organoehlorine and organophosphorus eompounds has bccn therefore needed in this eountry.…”
Section: Introductionmentioning
confidence: 99%
“…Continucd tiek control has rcsulted in the development of resistance to thesc chcmicals (5,10,13). A new acaricide wiıh a mode of aetion different from those of the organoehlorine and organophosphorus eompounds has bccn therefore needed in this eountry.…”
Section: Fanzago and Damalina Limbata Gervaü Onmentioning
confidence: 99%